Measurement of human abdominal and femoral intravascular adipose tissue blood flow using percutaneous Doppler ultrasound. (1st January 2021) - Lempesis, Ioannis G.; Goossens, Gijs H.; Manolopoulos, Konstantinos N.
ABSTRACT: Adipose tissue blood flow (ATBF) is an important determinant of adipose tissue (AT) function. 133 Xenon wash-out technique is considered the gold-standard for human ATBF measurements. However, decreasing 133 Xenon clinical use and costly production and preservation, make alternative (non-invasive) methods necessary. Here, we explored percutaneous Doppler ultrasound as a proxy method to quantify intravascular subcutaneous abdominal and femoral ATBF in humans ( n = 17). Both fasting ATBF and the postprandial increase in ATBF were significantly higher in abdominal compared to femoral AT. Although anatomical variations in vein location and depot thickness may impact feasibility, we demonstrate that Doppler ultrasound detects the expected depot-differences and postprandial increase in ATBF in healthy individuals. This method warrants further investigation in other populations and metabolic conditions.